Mortality of nitrate fertiliser workers. Issue 8 (August 1986) - Al-Dabbagh, S; Forman, D; Bryson, D; Stratton, I; Doll, R
Abstract : An epidemiological cohort study was conducted to investigate the mortality patterns among a group of workers engaged in the production of nitrate based fertilisers. This study was designed to test the hypothesis that individuals exposed to high concentrations of nitrates might be at increased risk of developing cancers, particularly gastric cancer. A total of 1327 male workers who had been employed in the production of fertilisers between 1946 and 1981 and who had been occupationally exposed to nitrates for at least one year were followed up until 1 March 1981. In total, 304 deaths were observed in this group and these were compared with expected numbers calculated from mortality rates in the northern region of England, where the factory was located. Analysis was also carried out separately for a subgroup of the cohort who had been heavily exposed to nitrates–that is, working in an environment likely to contain more than 10 mg nitrate/m3 for a year or longer. In neither the entire cohort nor the subgroup was any significant excess observed for all causes of mortality or for mortality from any of five broad categories of cause or from four specific types of cancer. A small excess of lung cancer was noted more than 20 years after first exposure in men heavily exposed for more than 10 years. That men were exposed to high concentrations of nitrate was confirmed by comparing concentrations of nitrates in the saliva of a sample of currently employed men with control men, employed at the same factory but not in fertiliser production. The men exposed to nitrate had substantially raised concentrations of nitrate in their saliva compared with both controls within the industry and with men in the general population and resident nearby. The results of this study therefore weight against the idea that exposure to nitrates in the environment leads to the formation in vivo of material amounts of carcinogens.